Peningkatan Hasil Belajar PKn Melalui Model Pembelajaran Meaningful Instructional Design - Rulla Manurung (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The purpose of this study is to determine the improvement of learning outcomes of Civics materials describing the Unitary State of the Republic of Indonesia with the implementation of learning model Meaningful Instructional Design. The subjects of this study are the students of grade V of Elementary School 017129 Silomlom academic year 2016/2017. Data obtained in the form of formative test results, observation sheet of teaching and learning activities. From the analysis result, it is found that students' learning achievement has increased from cycle I to cycle III, that is cycle I (50%), cycle II (66,67%), cycle III (91,67%). The conclusion of this research is the use of learning model Meaningful Instructional Design can improve the learning outcomes of Civics materials describing the Unitary State of the Republic of Indonesia on the students of grade V SD Negeri 017129 Silomlom Lesson Year 2016/2017 Keywords: meaningful instructional design, Unitary State of the Republic of Indonesia Abstrak: Tujuan penelitian ini adalah untuk mengetahui peningkatan hasil belajar PKn materi mendeskripsikan Negara Kesatuan Republik Indonesia dengan diterapkannya model pembelajaran Meaningful Instructional Design. Subjek penelitian ini adalah siswa kelas V SD Negeri 017129 Silomlom tahun pelajaran 2016/2017. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analisis didapatkan bahwa prestasi belajar siswa mengalami peningkatan dari siklus I sampai siklus III, yaitu siklus I (50%), siklus II (66,67%), siklus III (91,67%). Kesimpulan dari penelitian ini adalah penggunaan model pembelajaran Meaningful Instructional Design dapat meningkatkan hasil belajar PKn materi mendeskripsikan Negara Kesatuan Repu-blik Indonesia pada siswa kelas V SD Negeri 017129 Silomlom Tahun Pelajaran 2016/2017 Kata kunci: meaningful instructional design, Negara Kesatuan Republik Indonesia